Teacher Trainers’ Collaborative Reflections Based on an Inter-Institutional Self-Study; [Réflexion Collaborative D’Enseignants-Formateurs À Partir D’Une Self-Study Interinstitutionnelle]; [Reflexão Colaborativa de Didatas Com Base Em Um Self-Study Interinstitucional]; [Reflexión Colaborativa de Didactas Basada en Un Self-Study Interinstitucional] - Vanegas-Ortega, C (Fundacao Carlos Chagas, 2024)
This paper presents an exploratory self-study involving five teacher trainers from different countries, specialized in the teaching of science and mathematics. To characterize the community’s reflective processes, discussion groups were held during which recordings of their lessons were analyzed. Through a content analysis, we identified two types of interventions that facilitated dialogical reflection: questions leading to a deeper understanding of the practice of others and evaluations concerning its significant aspects. Moreover, the classroom pedagogical features associated to some theoretical elements seem to characterize the reflection content. Such reflective processes can give new meaning to the teacher trainers’ practice and show potential for professional development. © 2024, Fundacao Carlos Chagas. All rights reserved.